Analytical solutions of moisture‐chloride ion coupled transport in unsaturated concrete. Issue 11 (10th July 2021) - Wang, Yao; Bai, Yu; Xi, Yunping
Abstract: Studies of chloride‐induced corrosion in reinforced concrete structures are performed based on the reliable predictions of chloride and moisture distributions in concrete. This paper adopted the Laplace Transformation and the inverse Laplace Transformation to obtain the analytical solutions of the moisture‐chloride two‐way coupled transport processes. Additionally, the model has involved with realistic material parameters to predict the internal distributions of relative humidity and free chloride ions in concrete samples. To illustrate the accuracy of the present model, the calculations were compared with the available experimental results, and good agreements were obtained. It indicates that the present analytical model can successfully characterize the two‐way coupling effects between chloride transport and moisture diffusion in concrete; and the model can provide the distribution profiles of both chloride and relative humidity in concrete, which are useful for predicting the service life of reinforced concrete structures.